What are antenatal maternity care needs of women who conceived through fertility treatment?: a mixed methods systematic review - J. Catja Warmelink; Lisa Marissink; Linda Kroes; Fahimeh Ranjbar; Jens Henrichs (Taylor & Francis Group, 2023)
Background Existing research indicates that pregnant women who conceived through fertility treatment might experience more stress and anxiety compared to women who conceived spontaneously. Therefore, these women might have additional antenatal care needs. Methods A search for both quantitative and qualitative studies was performed in PubMed, PsycINFO, CINAHL and MEDLINE through May 2021, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. 21 articles met the inclusion criteria. After methodological quality appraisal using the Mixed Methods Appraising Tool, 15 studies were included in the review. Results Analysis of the studies identified behavioral, relational/social, emotional, and cognitive needs and women's preference about maternity care. Women who conceived through fertility treatment reported lower social and physical functioning scores and elevated levels of anxiety and depression compared to women who conceived spontaneously. They reported difficulties adjusting to pregnancy and experienced a care gap between discharge from the fertility clinic and going to local maternity care services for their first consultation, and a care gap postpartum. Conclusions Women who conceived through fertility treatment have additional antenatal care needs. We recommend to offer these women more frequent check-ins, and to pay attention to the impact of their infertility and treatment on their pregnancy.